Dismielinizações primárias no sistema nervoso central - Orlando Aidar (Arquivos de Neuro-Psiquiatria)
Diffuse sclerosis, neuromyelitis optica, multiple sclerosis, subacute combined degeneration and acute disseminated encephalomyelitis are briefly described from the anatomical point of view, especially with reference to their variations and to those of their interlocking aspects that point to a unitary concept of their pathogeny. Their features of similarity are compared to the changes described in cases of experimental allergic encephalomyelitis (Ferraro) produced in laboratory animals. Illustrations stress some of the features that are common to those diseases, either in their "typical" or "atypical" forms.